Taming the Complexity of Donor–Acceptor Stenhouse Adducts: Infrared Motion Pictures of the Complete Switching Pathway - Zulfikri, Habiburrahman (J Am Chem Soc, 2019)
[Image: see text] Switches that can be actively steered by external stimuli along multiple pathways at the molecular level are the basis for next-generation responsive material systems. The operation of commonly employed molecular photoswitches revolves around one key structural coordinate. Photoswitches with functionalities that depend on and can be addressed along multiple coordinates would offer novel means to tailor and control their behavior and performance. The recently developed donor–acceptor Stenhouse adducts (DASAs) are versatile switches suitable for such applications. Their photochemistry is well understood, but is only responsible for part of their overall photoswitching mechanism. The remaining thermal switching pathways are to date unknown. Here, rapid-scan infrared absorption spectroscopy is used to obtain transient fingerprints of reactions occurring on the ground state potential energy surface after reaching structures generated through light absorption. The spectroscopic data are interpreted in terms of structural transformations using kinetic modeling and quantum chemical calculations. Through this combined experimental–theoretical approach, we are able to unravel the complexity of the multidimensional ground-state potential energy surface explored by the photoswitch and use this knowledge to predict, and subsequently confirm, how DASA switches can be guided along this potential energy surface. These results break new ground for developing user-geared DASA switches but also shed light on the development of novel photoswitches in general.